Semi-homogeneous anion selective exchange membrane as well as preparation method and application thereof
By adopting anion-selective exchange membrane with semi-homogeneous structure, combining linear low-density polyethylene, quaternary ammonium functional ion exchange resin and amide group resin, the problems of harmful materials and poor electrochemical performance in the manufacturing process of existing anion exchange membrane materials are solved, and the effects of reducing membrane surface resistance, increasing migration number and improving equipment processing efficiency are achieved.
Patent Information
- Application Number
- CN202411930168.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-11
AI Technical Summary
The existing anion exchange membrane materials use harmful materials during the manufacturing process, which are difficult to chemically modify, have limited physical strength, and have poor electrochemical performance, and are limited in scope of application.
A semi-homogeneous anion selective exchange membrane with an amide group and a quaternary ammonium functional group were prepared by mixing linear low-density polyethylene, an ion exchange resin containing quaternary ammonium functional groups in proportion, and melt kneading, extrusion film forming and soaking treatment.
It has achieved reduced membrane surface resistance and increased migration number, and has temperature resistance, oxidation resistance and high strength properties. It is suitable for electrodialysis and electrodeionization equipment, improving ion exchange activity and equipment processing efficiency.
Smart Images

Figure CN119588436A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resin-based composite membrane materials, and in particular to a semi-homogeneous anion selective exchange membrane and a preparation method and application thereof. Background Art
[0002] Ion exchange membranes are an important ion separation material in the purification or treatment of water, food, beverages, chemicals and wastewater, as well as in equipment for fractionation, migration consumption and electrical regeneration, especially in electrodialysis and electrodeionization equipment (EDI). According to the differences in the structure of ion exchange membranes, they are divided into homogeneous ion exchange membranes and heterogeneous ion exchange membranes. Ion exchange membrane materials are also divided into anionic ion exchange membrane materials and anionic ion exchange membrane materials. Homogeneous membranes refer to the entire membrane, excluding any supporting materials that can be used to improve strength. The membrane is made of reactive polymers containing ion exchange functions. Homogeneous membranes are often difficult to manufacture. They use harmful materials during the manufacturing process. In addition, they are difficult to chemically modify. Each modification requires changing the basic chemical properties of the membrane. At the same time, the physical strength of homogeneous membranes is often limited. A screen or cloth is often required for support because the produced polymers cannot easily combine the required physical and electrochemical properties to operate effectively in the manufactured equipment. Heterogeneous membranes are composed of composite materials containing ion exchange resins to transfer electrochemical properties and binders that impart physical strength and integrity. They are generally formed by fusion of base membrane materials and ion exchange resins. A typical heterogeneous membrane may be a heterogeneous membrane produced by a paste process, and current heterogeneous membranes often have poor electrochemical performance.
[0003] U.S. Patent No. 5,037,858 discloses an anion selective polymer prepared from a concentrated solution of N,N'-methylenebisacrylamide. In this anion exchange membrane material, a positive nitrogen ion center is designed and introduced, but N,N'-methylenebisacrylamide is used alone. This substance is easy to precipitate during the engineering application of the membrane material, thereby causing the function of the membrane material to decay after a period of operation. In addition, this membrane material uses N,N'-methylenebisacrylamide, which has certain toxicity and is not suitable for use in some products and devices with high water quality requirements.
[0004] US Patent No. 7087654B2 discloses an ion exchange and electrochemical method and device using one-step quaternization and polymerization of anion selective polymers. This method also uses the anion exchange function of the positive nitrogen ion center. This is also a form of homogeneous membrane material. This homogeneous membrane material is difficult to chemically modify. Each modification requires changing the basic chemical properties of the membrane. In addition, the physical strength of the homogeneous membrane of this homogeneous membrane material is limited, and its cost is relatively high. The process is cumbersome.
[0005] US Patent No. 5137925A discloses an anion exchange membrane material with improved contamination resistance. The base membrane material used in the anion exchange membrane material is polyvinyl chloride, and an anion homogeneous membrane material with positive nitrogen ion centers and unsaturated double bonds is introduced into the polymer structure. The use of the unsaturated double bonds introduced into the membrane material is irreversible. At the same time, the homogeneous membrane material is difficult to be chemically modified. Each modification requires changing the basic chemical properties of the membrane. In addition, the physical strength of the homogeneous membrane of the homogeneous membrane material is limited, and its cost is relatively high. The process is cumbersome.
[0006] US Patent No. 4373031A discloses a membrane material using ditertiary amine to synthesize anion exchange polymers. The ditertiary amine material in this membrane material has certain toxicity and has certain solubility in hot water. Therefore, this membrane material is suitable for use at relatively low temperatures. In addition, the homogeneous membrane has no support layer and its physical properties are not very good.
[0007] U.S. Patent No. 4,374,720A discloses the synthesis of a water-soluble crosslinking agent and its use in the manufacture of anionic polymers. In this patent, chloroform is used in the process of preparing anionic polymers, which is also a homogeneous membrane material and has been gradually eliminated in the current membrane material preparation process. The method of the present invention uses a single ion exchange group positive nitrogen ion center group, and because the polymer has certain water solubility. The membrane surface resistance and ion migration number are not as good as those of the present invention. The ion exchange activity and capacity of this anion exchange membrane material are not as good as those of quaternary ammonium salt type ion exchange groups.
[0008] Chinese patent CN 115028956 A discloses an anion exchange membrane, a preparation method and the preparation and application of an alkaline anion exchange membrane. The patent also prepares a polycationic polymer. The anion exchange membrane and alkaline anion exchange membrane provided by the present invention have high ion conductivity, obvious hydrophilic and hydrophobic microphase separation structure and excellent chemical stability, and have good application prospects in the field of anion exchange membrane fuel cells. The solvent of the copolymer solution used in this patent is chloroform, dichloromethane or tetrahydrofuran, and the anion exchange membrane material uses N-methylpiperidine, N,N'-dimethylpiperazine, N,N-dimethylhexadecylamine, which all enhance the ion exchange capacity, but have greater toxicity. At the same time, these monomer substances have certain solubility under high temperature conditions, and they are used in the field of anion exchange membrane materials, and have certain limitations in the field of pure water preparation technology.
[0009] In order to overcome the problems existing in the preparation and application of anion exchange membrane materials, it is urgent to propose a new ion exchange membrane to solve the above problems. Summary of the invention
[0010] In order to solve the above problems, the present invention provides a semi-homogeneous anion selective exchange membrane and a preparation method and application thereof. The present invention provides the following technical solutions:
[0011] The invention discloses a method for preparing a semi-homogeneous anion selective exchange membrane. Linear low-density polyethylene, an ion exchange resin containing a quaternary ammonium functional group, a resin containing an amide group and an auxiliary agent are uniformly mixed in a predetermined ratio, and then melt-kneading, extruding into a membrane and soaking are performed in sequence to obtain the semi-homogeneous anion selective exchange membrane.
[0012] Further, the temperature of melt mixing and extrusion film forming is 150-180°C;
[0013] The extrusion film forming speed is controlled at 0.5-0.8m / min;
[0014] The soaking conditions are: soaking in a sodium chloride solution with a mass fraction of 4-5% at 23-25° C. for 46-50 hours.
[0015] Furthermore, the raw material components of the semi-homogeneous anion selective exchange membrane include, by weight, 1-1.1 parts of linear low-density polyethylene, 0.85-1.0 parts of ion exchange resin containing quaternary ammonium functional groups, 0.1-0.22 parts of resin containing amide groups and 0.03-1.0 parts of additives.
[0016] Further, the linear low density polyethylene is obtained by copolymerization of propylene, butene, 4-methyl-1-pentene, hexene or octene;
[0017] Among them, the relative molecular mass of linear low-density polyethylene is 50,000-100,000, and the density is 0.915-0.935 g / cm 3 , the melting point is 115-120℃.
[0018] Further, the water content of the ion exchange resin containing quaternary ammonium functional groups is less than 15%;
[0019] Ion exchange resins containing quaternary ammonium functional groups include polystyrene quaternary ammonium anion resins, beaded polystyrene anion exchange resins, and styrene divinylbenzene copolymer anion exchange resins.
[0020] Further, the amount of the resin containing amide groups is 1-20% by weight of the linear low-density polyethylene;
[0021] The resin containing an amide group includes a polyamide resin and / or a polyester polyurethane resin.
[0022] Further, the relative molecular mass of the polyamide resin is 8000-12000, the acid value is less than 10 mgKOH / g, the amine value is less than 5 mgKOH / g, the softening point temperature is 130-140° C., and the average particle size is 25±5 μm; and / or,
[0023] The relative molecular mass of polyester polyurethane resin is 5000-12000, the acid value is 30-35 mgKOH / g, the glass transition temperature is 40-65°C, the softening point temperature is 80-95°C, and the melting temperature is 150-160°C.
[0024] Furthermore, the auxiliary agent includes calcium stearate and 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, wherein:
[0025] The weight ratio of calcium stearate to 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is (0.1-0.5):(0.2-0.5).
[0026] The present invention also provides a semi-homogeneous anion selective exchange membrane prepared by the method as described above, wherein the thickness of the semi-homogeneous anion selective exchange membrane is 0.20 mm-1.00 mm.
[0027] The present invention also provides the use of the semi-homogeneous anion selective exchange membrane in electrodialysis and electrodeionization equipment.
[0028] Technical effects and advantages of the present invention:
[0029] The present invention proposes the development and industrialization of semi-homogeneous membrane materials. Semi-homogeneous ion exchange membranes are between homogeneous membranes and heterogeneous membranes. A part of its fixed groups is chemically bonded to the membrane matrix, and the electrochemical performance of the membrane is also between that of homogeneous membranes and heterogeneous membranes. The present invention is based on the use of ion exchange resins containing quaternary ammonium groups and base membrane resin materials containing amide groups to prepare a semi-homogeneous anion selective exchange membrane with amide groups and quaternary ammonium functional groups. A part of the fixed groups of this membrane is physically bonded to the polymer matrix, while another part of the fixed groups is chemically bonded to the polymer matrix, and the membrane has the characteristics of both heterogeneous membranes and homogeneous membranes.
[0030] Low molecular weight polyamide resin or polyester polyurethane resin with amide group, which contains positively charged nitrogen atom center, can not only provide weakly charged ion exchange groups, but also act as a lubricant to reduce the required extrusion or molding temperature, and is insoluble in water, thereby reducing the thermal damage to the ion exchange resin during the thermoforming process. This membrane material not only combines the advantages of homogeneous membrane and heterogeneous membrane, but also has a high migration number> 96%, membrane surface resistance< 12Ω.cm 2, heat resistance, oxidation resistance, high strength and other properties. It is a membrane material with better engineering applications. The test results show that the membrane surface resistance and migration number of the semi-homogeneous ion exchange membrane material prepared by the present invention are greatly improved. The membrane is also used in electrochemical equipment, such as alkali / chlorine electrolysis equipment, electrophoretic paint purification equipment and electro-organic synthesis equipment, etc., and is particularly suitable for electrodialysis and electrodeionization equipment (EDI).
[0031] The main materials used in the present invention, due to the use of low molecular weight polyamide resin and (or) polyester polyurethane resin that play a lubricating role in processing performance, not only play the role of improving the processing performance of linear low density polyethylene and improving the lubrication processing performance in the process of LLDPE and anion exchange resin mixed film formation, but also can provide positively charged selective ion exchange groups, and can also play the role of anion exchange resin. The ion exchange active points of the anion exchange membrane material are effectively improved, and the addition of the amide resin makes the ion exchange resin wet the surface during the activation process, and the specific surface area is larger, so that more ion exchange resin materials can be exposed to the treatment fluid in the equipment using the membrane, so the ion exchange membrane material can obtain excellent ion exchange performance within the thickness range of 0.20mm-1.00mm, and the addition of the amide resin makes the membrane surface resistance of the anion exchange membrane material lower and the migration number higher.
[0032] The anion exchange membrane material has stronger anion adsorption and exchange capabilities, thus forming an anion semi-homogeneous selective exchange membrane with amide and quaternary ammonium functional groups. In short, this anion semi-homogeneous anion exchange membrane material has low membrane resistance, high migration number, and has the properties of temperature resistance, oxidation resistance, and good dimensional stability.
[0033] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by implementing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a sample diagram of the extrusion molding process using 10% low molecular weight polyamide resin in Example 1 of the present application;
[0035] Figure 2 This is a sample diagram of the extrusion molding process using 10% low molecular weight polyester polyurethane resin in Example 2 of the present application;
[0036] Figure 3 It is a sample of the extrusion molding process using 5% low molecular weight polyamide resin + 5% polyester polyurethane resin according to Example 3 of the present application;
[0037] Figure 4For the sample of the extrusion molding process without using low molecular weight polyamide resin and polyester polyurethane resin in Example 4 of the present application;
[0038] Figure 5 This is a sample of the extrusion molding process without adding resin produced by a foreign company in the prior art of comparative example 5 of this application. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] In order to solve the deficiencies of the prior art, the present invention discloses a semi-homogeneous anion selective exchange membrane. The raw material components of the semi-homogeneous anion selective exchange membrane include, by weight, 1-1.1 parts of linear low-density polyethylene (LLDPE), 0.85-1.0 parts of an ion exchange resin containing a quaternary ammonium functional group, 0.1-0.22 parts of a resin containing an amide group and 0.03-1.0 parts of an auxiliary agent (the formula of the auxiliary agent contains 0.1-0.5 parts of calcium stearate and 0.2-0.5 parts of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol ester).
[0041] In a specific embodiment of the present invention, linear low-density polyethylene is produced by copolymerization of propylene, butene, 4-methyl-1-pentene, hexene or octene. These mixed monomers undergo free radical polymerization, and short chain branches are present in the polymer to form a combination of linearity and low density. This type of LLDPE membrane material has smoothness and hydrophobicity. These characteristics simplify the filling of ion exchange resins in the process of preparing ion exchange membrane materials and eliminate the content of extractables in adhesives. This membrane material is an advantage in producing ultrapure water in electrodeionization devices. It is an ideal base membrane material for preparing high-quality ion exchange membrane materials.
[0042] In a specific embodiment of the present invention, the anion exchange resin containing quaternary ammonium functional groups has a water content of 10-20%, preferably less than 15%. For example, the anion exchange resin material used is a beaded polystyrene quaternary ammonium anion resin containing 8-10% DVB copolymerized by styrene and divinylbenzene, which has a white powder appearance and a size of about 50 μm, and its functional group is NH4 + , moisture content 10-20%.
[0043] Ion exchange resins containing quaternary ammonium functional groups also include beaded polystyrene anion exchange resins and styrene-divinylbenzene copolymerized anion exchange resins. Among them, the beaded polystyrene anion exchange resin has a size of 300-1200 μm, and the anion active group is chloride ion;
[0044] The anion exchange resin of styrene divinylbenzene copolymer can be a macroporous anion exchange resin of styrene divinylbenzene copolymer produced by DuPont Company, with a size of 650-820 μm and an anion active group being chloride ion.
[0045] In a specific embodiment of the present invention, the amount of the resin containing amide groups is 1-20% of the weight of the linear low-density polyethylene; the resin containing amide groups includes polyamide resin and / or polyester polyurethane resin. Among them, the low-molecular-weight polyamide resin containing amide groups is a resin that can be melt-processed at a relatively low temperature, and it is formed by the ring-opening polymerization of caprolactam. The main technical indicators of this low-molecular-weight polyamide resin are as follows: the relative molecular mass is generally around 10,000, the preferred relative molecular mass is 8000-12000, the acid value is controlled at <10mgKOH / g, the amine value is controlled at <5mgKOH / g, the softening point temperature is 130-140°C, and the average particle size is 25±5μm. Compared with other polymer materials, this low melting point characteristic allows it to melt at a lower temperature, making it easier to handle and process.
[0046] Polyester polyurethane resin is a kind of rigid polyurethane resin material with excellent thermal insulation performance, chemical resistance, good electrical properties, easy processing and low water absorption. It is made by condensation polymerization of isocyanate MDI and polyester polyol. Its relative molecular mass is 5000-12000, the acid value is controlled at 30-35mgKOH / g, the glass transition temperature is 40-65℃, the softening point is 80-95℃, and the optimal melting temperature is 150-160℃. This amide-based resin brings a new weakly electropositive nitrogen atom center, which has a weak anion exchange function under certain conditions. It can improve the ion exchange and migration ability of the anion selective exchange membrane, and also reduce the membrane resistance. Like the aforementioned low molecular weight polyamide resin, the polyester polyurethane resin used can also be used as a base membrane material while providing chemically bonded ion exchange groups, and act as a lubricant in the preparation and molding process of the base membrane material. We can also use any one or a combination of these two water-insoluble amide-based resin materials containing positive nitrogen ion centers.
[0047] In a specific embodiment of the present invention, the auxiliary agent includes calcium stearate and 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, wherein the weight ratio of calcium stearate to 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is (0.1-0.5):(0.2-0.5).
[0048] Anion exchange membrane is an ion exchange membrane material that selectively allows anions to pass through and be adsorbed, while blocking and rejecting other cations. Quaternary ammonium functional group anion exchange is a common exchange method for anion membrane materials. The exchange membrane material of the present invention is an ion exchange membrane material that not only physically fixes the membrane-like polymer matrix and the quaternary ammonium functional group, but also chemically fixes the polymer matrix and the amide group. It is called a semi-homogeneous anion selective exchange membrane material. Preferably, the raw material composition of the present invention mainly uses a relative molecular mass of 50,000-100,000 and a density of 0.915-0.935 g / cm 3 , a linear low-density polyethylene (LLDPE) with a melting point of 115-120°C and an ion exchange resin containing a quaternary ammonium functional group. In order to further improve the performance of the anion selective exchange membrane, the present invention also uses a low molecular weight polyamide resin and (or) polyester polyurethane resin containing an amide group with a similar melting molding processing temperature to LLDPE. The common feature of these two amide group-containing resins is that the amide group containing a nitrogen positive ion center is attached to the polymer framework and has an ion exchange function under certain conditions. This amide group-containing resin has a molding processing temperature and moldability similar to that of linear low-density polyethylene LLDPE, and is insoluble in water. The resin containing an amide group can provide a weakly positive amide group, provide an anion exchange active point in the base membrane material, and make the anion exchange membrane material have stronger anion adsorption and exchange capacity, especially higher exchange capacity for weakly electrolytic ions. It can also be used as a base film material to improve the lubrication processing performance in the mixed manufacturing process of LLDPE and quaternary ammonium functional group anion exchange resin, so that the anion exchange resin containing quaternary ammonium functional groups is more easily evenly dispersed in the LLDPE / low molecular weight polyamide resin and (or) polyester polyurethane resin matrix in the simple extrusion processing equipment we use. In addition, since the resin containing amide groups contains more polar groups, the ion exchange resin is soaked in the surface during the activation process, and the specific surface area of the base film material is larger, so that more ion exchange resin materials can be exposed to the processing fluid of the equipment using the membrane, so the ion exchange membrane material obtains excellent ion exchange performance within a thickness of, for example, 0.20-1.00mm. This semi-homogeneous anion exchange membrane material has lower membrane surface resistance and higher migration number, and has the properties of heat resistance, oxidation resistance and good dimensional stability.
[0049] The semi-homogeneous anion selective exchange membrane material of the present invention provides a relatively large specific surface area and abundant ion exchange active sites, so that it has stronger adsorption and exchange capacity in ion exchange. While isolating gas permeation and water permeation, this membrane material has the properties of high selectivity, low ion diffusion resistance, high physical strength and good chemical resistance. In addition, this membrane material does not use or produce harmful substances during the preparation process. This membrane material is easy to manufacture and has low processing cost. At the same time, the assembly preparation technology process of this membrane is simple and low in cost. In addition to the cost of raw materials, the manufacture of the membrane of the present invention adopts the steps of formulation, extrusion or heat treatment and brine conditioning, all of which use standard low-cost manufacturing equipment. It can be achieved without special equipment design and upgrading.
[0050] The semi-homogeneous anion selective exchange membrane of the present invention is used in electrodialysis and electrodeionization equipment, and is widely used in the fields of semiconductors, biomedicine, petrochemicals, thermal power generation, zero pollution discharge, brackish water and seawater desalination to prepare pure water or / and ultrapure water.
[0051] The present invention also provides a method for preparing a semi-homogeneous anion selective exchange membrane, which comprises the following steps: uniformly mixing linear low-density polyethylene, an ion exchange resin containing a quaternary ammonium functional group, a resin containing an amide group and an auxiliary agent in a predetermined ratio, and then sequentially performing melt mixing, extrusion into a membrane and soaking to obtain a semi-homogeneous anion selective exchange membrane.
[0052] In a specific embodiment of the present invention, during the preparation process, linear low-density polyethylene (LLDPE), ion exchange resin containing quaternary ammonium functional groups, low molecular weight polyamide resin containing amide groups and (or) polyester polyurethane resin and additives are first melted and mixed in a certain proportion, and then extruded using a screw extruder. A mold of the required thickness is installed at the end of the extruder, and the film is drawn and immersed in a 5% sodium chloride solution at 25°C for adjustment and activation of the membrane; the immersion conditions are: immersion in a 4-5% sodium chloride solution at 23-25°C for 46-50 hours. Preferably, the linear low-density polyethylene: anion exchange resin: amide group-containing resin is mixed and dried in a mass ratio of 100:85-95:5-20, and an extruder is used for extrusion processing. During the processing, the extrusion speed is controlled at 0.5-0.8 m / min, the melting and film forming are carried out in the range of 150-180° C., and the extruded film thickness is set to 0.20-1.00 mm. After film formation, the membrane material is immersed in a 5% sodium chloride solution at 25° C. for 48 hours to adjust and activate the membrane, thereby obtaining a semi-homogeneous anion selective exchange membrane having amide groups and quaternary ammonium functional groups.
[0053] No harmful substances are used or produced in the production and preparation process of this semi-homogeneous anion selective exchange membrane. The selected resin containing amide groups has a suitable glass transition temperature and softening point temperature. In the process of melting and mixing LLDPE and ion exchange resin, the addition of amide-containing resin can reduce the extrusion molding temperature required for the membrane material, thereby reducing the thermal damage to the ion exchange resin during the thermoforming process. It is simple, effective and low-cost. This anion exchange membrane material can be easily modified with membrane chemicals. Any commercially available ion exchange resin can be used as an ion exchange active point. It is a semi-homogeneous anion selective exchange membrane material with high efficiency and good performance.
[0054] The technical solution of the present invention will be further described below in conjunction with specific implementation methods.
[0055] Example 1
[0056] Weigh 450 parts of linear low-density polyethylene (model LLDPEDFDA9085), 550 parts of anion exchange resin, 45 parts of amide-containing low-molecular-weight polyamide resin, 0.2 parts of calcium stearate and 0.5 parts of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1076), mix and dry, use an extruder to extrude, control the extrusion speed to 0.5-0.8 m / min during the process, melt and film forming at 150-180° C., the film thickness after extrusion is 0.72 mm, put the membrane material into a 25° C. mass fraction 5% sodium chloride solution and soak for 48 hours to adjust and activate the membrane, and obtain a semi-homogeneous anion selective exchange membrane with amide and quaternary ammonium functional groups ( Figure 1 ).
[0057] Example 2
[0058] Weigh 450 parts of linear low-density polyethylene (model LLDPEDFDA9085), 550 parts of anion exchange resin, 45 parts of polyester polyurethane resin, 0.2 parts of calcium stearate and 0.5 parts of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1076) for mixing and drying, and use an extruder for extrusion processing. During the processing, the extrusion speed is controlled at 0.5-0.8 m / min, and the melting and film forming are carried out in the range of 150-180° C. The film thickness after extrusion is 0.72 mm. The membrane material is immersed in a 5% by mass sodium chloride solution at 25° C. for 48 hours to adjust and activate the membrane, and the obtained semi-homogeneous anion selective exchange membrane having amide groups and quaternary ammonium functional groups ( Figure 2 ).
[0059] Example 3
[0060] Weigh 450 parts of linear low-density polyethylene (model LLDPEDFDA9085), 550 parts of anion exchange resin, 22.5 parts of low molecular weight polyamide resin containing amide group, 22.5 parts of polyester polyurethane resin, 0.2 parts of calcium stearate and 0.5 parts of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1076) for mixing and drying, and use an extruder for extrusion processing. During the processing, the extrusion speed is controlled at 0.5-0.8m / min, and the melting and film forming are carried out in the range of 150-180℃. The thickness of the film after extrusion is 0.72mm. The membrane material is immersed in a sodium chloride solution with a mass fraction of 5% at 25℃ for 48 hours to adjust and activate the membrane. The obtained semi-homogeneous anion selective exchange membrane with amide group and quaternary ammonium functional group ( Figure 3 ).
[0061] Comparative Example 1
[0062] Weigh 450 parts of linear low-density polyethylene (model LLDPEDFDA9085), 550 parts of anion exchange resin, 0.2 parts of calcium stearate and 0.5 parts of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1076), mix and dry, use an extruder to extrude, control the extrusion speed to 0.5-0.8 m / min during the process, melt and film forming at 150-180° C., the film thickness after extrusion is 0.72 mm, put the membrane material into a 25° C. mass fraction 5% sodium chloride solution and soak for 48 hours to adjust and activate the membrane, and obtain a semi-homogeneous anion selective exchange membrane with amide group and quaternary ammonium functional group ( Figure 4 ).
[0063] Comparative Example 2
[0064] The heterogeneous anion exchange membrane material purchased from IONPURE Company on the market.
[0065] Examples 1-3, Comparative Example 1 and the existing IONPURE heterogeneous anion exchange membrane materials on the market ( Figure 5 ) were analyzed, and the main evaluation and comparison indicators were membrane thickness, ion exchange capacity mmol / g, internal resistance (Ω.CM 2 ), migration number%. The test results of the main ion exchange capacity and effect evaluation are shown in Table 1-2.
[0066] Table 1 Anion semi-homogeneous anion exchange resin membrane material formula, unit, parts
[0067]
[0068] Table 2 The performance analysis of anion semi-homogeneous anion exchange membrane materials is as follows:
[0069]
[0070] The test results of the ion exchange capacity, membrane surface internal resistance and migration number of the membrane material show (Table 2) that the addition of low molecular weight polyamide resin and (or) polyester polyurethane resin containing amide groups can reduce the membrane internal resistance of the ion exchange membrane material and increase the migration number. In the anion exchange resin with polyethylene as the base membrane material, the membrane internal resistance is relatively high. Adding additives can improve the processing, but it does not improve the membrane surface internal resistance. The present invention adopts the method of adding low molecular weight polyamide resin and (or) polyester polyurethane resin with amide groups to improve the membrane surface resistance and migration number. Table 2 contains a comparison of typical values of commercial anion exchange membrane materials from different manufacturers compared with the present invention. It can be seen from Table 2 that the internal resistance of the semipermeable membrane prepared by the method of the present invention is less than or equal to the heterogeneous anion exchange membrane material of IONPURE Company, and the internal resistance is low, indicating that the total power consumption of this membrane material in the water treatment process will be greatly reduced, and the migration number will be slightly improved. The anion exchange membrane material ion exchange membrane related to the present invention has similar permeability selectivity and permeability as other commercially available membranes. When the membrane thickness and ion exchange resin ratio are basically the same, the semi-homogeneous membrane prepared by the present invention has lower membrane internal resistance and higher ion migration number.
[0071] The main materials used in the present invention, such as linear low-density polyethylene, anion exchange resin, low molecular weight polyamide resin and (or) polyester polyurethane resin, are all main materials available in the commercial market. Among them, the low molecular weight polyamide resin and (or) polyester polyurethane resin are set according to the needs, and the product technical indicators are set. The use and type of these materials cannot be understood as a limitation on this aspect because of a slight change in their technical indicators. The terms used in the present invention should be understood to have the same meaning as these terms in the context of this specification and the relevant field, and should not be understood in an idealized or overly formal sense, except for the explicit definition in the present invention. These and other objects and features of the present invention are described in detail and more fully in the attached drawings of the present invention.
[0072] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a semi-homogeneous anion selective exchange membrane, characterized in that: The method comprises: Linear low-density polyethylene, ion exchange resin containing quaternary ammonium functional groups, resin containing amide groups and additives are uniformly mixed in a predetermined ratio, and then melt-kneaded, extruded into membranes and soaked in sequence to obtain a semi-homogeneous anion selective exchange membrane.
2. The method for preparing a semi-homogeneous anion selective exchange membrane according to claim 1, characterized in that: The temperature for melt mixing and extrusion film forming is 150-180°C; The extrusion film forming speed is controlled at 0.5-0.8m / min; The soaking conditions are: soaking in a sodium chloride solution with a mass fraction of 4-5% at 23-25° C. for 46-50 hours.
3. The method for preparing a semi-homogeneous anion selective exchange membrane according to claim 1, characterized in that: The raw material components of the semi-homogeneous anion selective exchange membrane include, by weight, 1-1.1 parts of linear low-density polyethylene, 0.85-1.0 parts of ion exchange resin containing quaternary ammonium functional groups, 0.1-0.22 parts of resin containing amide groups and 0.03-1.0 parts of auxiliary agents.
4. The method for preparing a semi-homogeneous anion selective exchange membrane according to claim 1, characterized in that: Linear low-density polyethylene is obtained by copolymerization of propylene, butene, 4-methyl-1-pentene, hexene or octene; Among them, the relative molecular mass of linear low-density polyethylene is 50,000-100,000, and the density is 0.915-0.935 g / cm 3 , the melting point is 115-120℃.
5. The method for preparing a semi-homogeneous anion selective exchange membrane according to claim 1, characterized in that: The water content of the ion exchange resin containing quaternary ammonium functional groups is 10-20%; Ion exchange resins containing quaternary ammonium functional groups include polystyrene quaternary ammonium anion resins, beaded polystyrene anion exchange resins, and styrene divinylbenzene copolymer anion exchange resins.
6. The method for preparing a semi-homogeneous anion selective exchange membrane according to claim 1, characterized in that: The amount of the resin containing amide groups is 1-20% by weight of the linear low-density polyethylene; The resin containing an amide group includes a polyamide resin and / or a polyester polyurethane resin.
7. The method for preparing a semi-homogeneous anion selective exchange membrane according to claim 6, characterized in that: The relative molecular weight of the polyamide resin is 8000-12000, the acid value is less than 10 mgKOH / g, the amine value is less than 5 mgKOH / g, the softening point temperature is 130-140°C, and the average particle size is 25±5 μm; and / or, The relative molecular mass of polyester polyurethane resin is 5000-12000, the acid value is 30-35 mgKOH / g, the glass transition temperature is 40-65°C, the softening point temperature is 80-95°C, and the melting temperature is 150-160°C.
8. The method for preparing a semi-homogeneous anion selective exchange membrane according to claim 1, characterized in that: The auxiliary agent includes calcium stearate and 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, wherein: The weight ratio of calcium stearate to 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is (0.1-0.5):(0.2-0.5).
9. A semi-homogeneous anion selective exchange membrane prepared by the method according to any one of claims 1 to 8, characterized in that: The thickness of the semi-homogeneous anion selective exchange membrane is 0.20 mm-1.00 mm.
10. Use of the semi-homogeneous anion selective exchange membrane according to claim 9 in electrodialysis and electrodeionization equipment.
Citation Information
Patent Citations
Anion exchange membrane, preparation method and preparation and application of alkaline anion exchange membrane
CN115028956A
Synthesis of anion exchange polymers employing ditertiary amines
US4373031A
Synthesis of water soluble cross-linkers and their use in the manufacture of anionic polymers
US4374720A
Anion selective polymers prepared from concentrated solutions of N,N'-methylenebisacrylamide
US5037858A
Aliphatic anion exchange polymeric membranes having improved resistance to fouling
US5137925A